Resistance Spot Welding of SUS316L Austenitic/SUS425 Ferritic Stainless Steels: Weldment Characteristics, Mechanical Properties, Phase Transformation and Solidification - Teerawut Khuenkaew; Kannachai Kanlayasiri (My University, 2019)
This research examines the weldment characteristics and mechanical properties of lap joints of SUS316L/SUS425 stainless steels using resistance spot welding under variable weld currents and welding times. The weld current was varied between 7.0, 8.5, and 10.0 kA, and the welding time between 25, 38, and 50 cycles. The weldment quality characteristics under study were the depth of fusions, indentation depths, and nugget diameter, and the mechanical properties included the tensile shear force (TSF) and micro Vickers hardness. Phase transformation and solidification were characterized using scanning electron microscopy and energy dispersive X-ray spectrometry, together with Schaeffler and pseudo-binary predictive phase diagrams. The results revealed that the weldment quality was positively correlated with weld current and welding time, as were the TSF and micro hardness. The optimal welding condition was achieved under a 10.0 kA weld current and 25-cycle welding time. Under the optimal condition, the fusion zone exhibited compression-direction columnar grains consisting of austenite, ferrite, and martensite and the solidification was of ferrite plus Widmanstatten austenite.
Keywords: Indentation; Spot welding; Advanced Welding Techniques Analysis